(untitled) (Studia Prawnicze / The Legal Studies, 1963)
As one of the government management elements, coordination is a legal institution aimed at ensuring the harmonious functioning of entities subject to coordination (settlement, preventing them in the future, eliminating unnecessary activity duplication, etc.). It includes various areas of social activity; in particular, it covers the area of economic activity. The coordination of the economic relations plays a particularly important role in a socialist state with controlled economy. On the one hand, this is due to the growth of this type of the government tasks in the economy and expansion of the economic apparatus associated with it, and, on the other hand, it is due to the introduction of the planned economy. After all, a great expansion of the economic apparatus is fraught with the danger of discord in activity while the principle of the planned economy requires just the harmonization and coordination of various actions of entities establishing economic functions, which is a condition for both planning and its implementation. The functions of economic coordination are performed by a number of state bodies, including the people’s councils. It is in the nature of things that the coordination functions of the people’s councils are limited to the unit of the administrative division where this council operates. The purpose and criteria of this coordination boil down to a reasonable correlation between the needs of this region and national economic tasks. Although all councils can develop coordinating economic activities, but the greatest role in this respect belongs to the voivodeship people’s councils. A wide range of activity is spread out before these councils, various entities develop their activities there, and therefore, to a greater extent than anywhere else, the discrepancies in the actions of these entities may be here. Although all bodies at this level (plenary session, commissions, presidium, departments) can engage in coordinating economic activities; however, according to the provisions of the law on the people’s councils, the presidiums of these councils are vested with the greatest coordination powers. At the same time, according to this law, each body of the council plays only its own role in economic coordination. Finally, the coordinating activities of the council and its bodies cover various entities: organizational units that develop economic activities and are part of the council apparatus, as well as organizational units that are not the part of the council apparatus. In both cases, the coordinating activity is distinguished by a number of specific features. The economic coordination of the council apparatus is facilitated by the structure of this apparatus based on the principle of democratic centralism. This principle results in conclusions regarding ensuring the unity and coordination of the council actions which are essential in the context of the coordination competence. It also follows from this principle that the functions of economic coordination will be carried out in the council apparatus on two planes: on the “horizontal” plane and on the “vertical” plane. In case of “horizontal” coordination, it is necessary to organize the harmonious fulfilment of economic tasks by the entire apparatus of the council at this level. At the same time, the “horizontal” coordination should primarily take into account the point of view and economic interests of this region. The provisions of law usually do not contain special guidance regarding the forms and means of this coordination. Therefore, the bodies of the councils will use here, first of all, public forms and means within the framework of “horizontal jurisdiction”. The powers of the presidiums entrusted to their departments dealing with economic problems and the powers in relation to local enterprises (exercised on a voivodeship scale through the respective associations) should play the most important role in this type of coordination. The “vertical” economic coordination is a kind of continued coordination carried out by the respective central bodies. It applies to tasks that require a uniform solution on the basis of a district, voivodeship or the entire state and should only concern the issues of cardinal or national importance. This is explained by the fact that the “vertical” economic coordination is a demonstration of centralism in the system of democratic centralism. It will be carried out through the various forms and means in various groups of the council bodies (in the group of councils, presidiums and departments). The economic coordination carried out by the council and its bodies in relation to organizational units outside the council apparatus covers a wide range of entities: state organizational units managed from the centre, cooperatives, and even subjects of non-socialized economy. Here, we are only interested in the economic coordination regarding the state organizational units that develop their activities in the territory of this council. The basis for the coordination functions of the councils in relation to this group of entities is the interdependence between the local economy and the economy managed from the centre; the basis for the implementation of this competence by the councils is their function of government management in the area of their activity. However, the numerous forms and means provided to the council bodies by the law of 1958 and the related regulations cannot violate the organizational independence of the state units governed from the centre.